The Credit Spread: Risk-Free Rate in the Model - GHAZARYAN, Amasya; ASOYAN, Satine; MELIK-PARSADANYAN, Vahagn (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024DO - 10.14505/tpref.v15.3(31).11, 2024)
This paper proposes a parsimonious credit spread estimation model for valuation of corporate bonds in data-scarce markets. We emphasize the importance of incorporating the risk-free rate directly into credit spread determination. Our model aligns with established literature and demonstrates the ability to capture the observed influence of risk-free rates on credit spreads across economies. We posit that models omitting the risk-free rate component may underestimate credit spreads, particularly impactful in emerging markets with elevated default probabilities and high risk-free rates. Finally, we discuss practical applications of the model, including exchange rate premium calculations, policy analysis, and negative yield spread analysis.